Alyssa Ayres, Speaking Like a State. Language and Nationalism in Pakistan - Varini, Marta (Bhasha)
Review of Ayres, A. (2009). Speaking Like a State. Language and Nationalism in Pakistan. New York: Cambridge University Press, 217 pp.